2021
DOI: 10.2147/cmar.s307753
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acid is a Promising Biomarker in Triage Screening for Patients with Colorectal Cancer: A Case–Control Study

Abstract: The aim of our study was to identify the diagnostic ability of free fatty acids (FFAs) in younger colorectal cancer (CRC) patients by comparing carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA19-9). Methods: Patients screened for CRC at Fujian Medical University Union Hospital from January 2011 to December 2014 were recruited. Patients pathologically diagnosed with CRC or colorectal adenoma (CA) and healthy control participants were included. The enzyme endpoint method was applied to measure FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous results conducted by our research group in a large European population revealed that circulating bacterial DNA load was associated with fatty acid (FFA) levels and leukocyte count, [ 22 ] which represent common biomarkers with diagnostic or prognostic value in CRC [ 23 , 24 , 25 ]. Since the presence of the circulating microbiome in blood has been reported under both physiological and pathological conditions, the detection of altered circulating bacterial DNA could serve as a promising non-invasive biomarker for cancer detection tools.…”
Section: Introductionmentioning
confidence: 99%
“…Previous results conducted by our research group in a large European population revealed that circulating bacterial DNA load was associated with fatty acid (FFA) levels and leukocyte count, [ 22 ] which represent common biomarkers with diagnostic or prognostic value in CRC [ 23 , 24 , 25 ]. Since the presence of the circulating microbiome in blood has been reported under both physiological and pathological conditions, the detection of altered circulating bacterial DNA could serve as a promising non-invasive biomarker for cancer detection tools.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] An epidemiological study showed that free fatty acids (FFA) levels can complement the predictive ability of CEA and CA19-9 and differentiate them from TNM staging. 11 These are associated with cancer by numerous metabolic pathways 4 and often by the growth and proliferation of FFA and HDL-C that meet energy requirements. 5 More particularly, high cholesterol demand is essential for tumor proliferation and OS in different types of endocrine cancers, including HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Free fatty acids (FFAs) are triacylglycerol (TG) precursors that are needed to replenish TG stores in adipose, liver and muscle tissue through esteri cation; when hepatic glycogen is low and muscles need energy, the TGs in adipose tissue are broken down into FFAs for energy (Stich and Berlan 2004). FFAs are overexpressed in colorectal patients (Zhu et al 2021), and abnormal fatty acid metabolismis associated with tumour cell metastasis in various cancers, including colorectal cancer (Kawaguchi et al 2016;Zhang et al 2020). High-density lipoprotein (HDL) is responsible for the reverse transport of cholesterol from peripheral cells to the liver, and associated apolipoproteins and enzymes can also exert antioxidant, antiin ammatory, antiangiogenic, antiapoptotic and immunomodulatory activities, resulting in overall antitumorigenic effects (Ganjali et al 2019).…”
Section: Introductionmentioning
confidence: 99%